ANALYSIS OF COMMUNITY INVOLVEMENT IN ECOTOURISM DEVELOPMENT PLANNING FOR MOUNT GEULIS SUMEDANG, WEST JAVA. - Annisa Lazuardina (Journal Hotspot, 2024)
This study aims to identify and analyze the model of involvement that can be realized by the community in managing the potential of the surrounding environment to be used as a tourist area. This study uses a qualitative approach, the population in this study are 8 (eight) villages around Mount Geulis, Sumedang, West Java. The tourism sector at this time continues to grow, one of which is nature-based tourism. Conventional tourism development carried out on natural tourist attractions certainly has a negative impact, especially on the surrounding environment both physically, culturally, and the community's economy. In an effort to minimize the negative impacts that may arise due to the development, a concept is needed that plans development to prioritize sustainability and environmental insight. One concept that can be used in running sustainable tourism is ecotourism. Various potentials found in this research can be packaged in an environmentally friendly tour. Various kinds of local wisdom that have been implemented and running need to be further improved so that they lead to improving regional welfare. The potential of human resources in each village around Mount Geulis has enough potential that can be developed as an area that can support the presence of ecotourism at Mount Geulis. This research uses descriptive qualitative methods by conducting in-depth interviews. This research will also find potential that may not have been realized by the government and local residents to be developed as tourism potential. The results of this research are a description of the main tasks and functions that already exist, which can be utilized as much as possible to support the existence of the Mount Geulis Geulis Tourism Area.